FACTORS IN THE FORMATION OF GENDER STEREOTYPES IN ADOLESCENTS (Universal International Scientific Journal, 2026)
This article analyzes the influence of gender stereotypes on the process ofadolescent personality formation based on modern psychological theories. The study examines theimpact of traditional perspectives formed within the family, educational institutions, and mediaenvironments on adolescents' self-esteem and career choices. The article concludes with scientificrecommendations for creating a psychological environment free from gender constraints to expandthe “ zone of proximal development” of the individual.
Keywords: Gender stereotypes; adolescence; personality formation